Penerapan model pembelajaran problem based learning untuk meningkatkan kemampuan berpikir dan hasil belajar siswa pada pembelajaran IPS di MTs KH Hasyim Asy’ari Malang - Sofi, Natilatus (Maliki Interdisciplinary Journal, 2024)
The aim of this research is to find out how well the Problem Based Learning (PBL) paradigm works in improving the learning outcomes of students who study demand, supply, markets and prices in subjects at MTS Kh. Hasyim Asy’ari Malang, class VII B. Classroom Action Research (PTK) was carried out in two cycles for this research. Class VII B students at MTs KH. Hasyim Hasyim Asy’ari Malang who was used as the research subject. The data analysis method uses a descriptive approach. Data is collected using test equipment. The research results showed that although learning implementation in cycle I was 59.5%, in cycle II there was an increase to 81%. Only 10 of the 24 students in the first cycle of learning completed the test with a percentage of 41%; in the second cycle, the number of students increased to 23, and their final grade had a completion rate of 96%. These findings show how a problem-based learning approach can improve the analytical abilities and output of social studies knowledge acquisition by students.